WITHIN THE PERIOD TO MEET THE DEADLINE: CZECH NEAR-SYNONYMS DOBA AND LHŮTA AND THEIR ENGLISH EQUIVALENTS - KLABAL, Ondřej (Comparative Legilinguistics, 2017)
The Czech Civil Code has recently introduced differentiation between two terms denoting a period of time: lhůta and doba. Both of these terms are used, often interchangeably, in ordinary Czech language and are thus susceptible to failure by translators to be recognized as terms. It is believed that the definitions provided by the draftsmen of the said code do not describe the difference in meaning sufficiently for non-lawyers to understand (cf. Goźdź-Roszkowski, 2013: 100). Therefore, this paper aims at describing the difference in meaning of these terms on the basis of a qualitative analysis of their collocational patterns and collocational profile, as used in the wording of the said law. The second part of the paper consists of an analysis of potential English equivalents (time limit, period, deadline, time) and their collocates as used in legislation drafted in English. The analysis is based on a corpus compiled of the Czech Civil Code and a comparable corpus of civil legislation drafted in English. The findings of the analysis will outline the strategies available to translators dealing with temporal expressions at the Czech-English interface.